Analysis of the success of MSMEs in West Medan through entrepreneurial behavior and competitive advantage - Eko Wahyu Nugrahadi; Muammar Rinaldi (Jurnal Mantik, 2024)
This research aims to determine the influence of entrepreneurial behavior and competitive advantage on the success of grocery MSMEs in Medan Barat Subdistrict. This research uses descriptive and quantitative methods and data sources in the form of primary and secondary data. The population in this research is all grocery MSME owners in every sub-district in West Medan District in 2023. The total sample is 188 grocery MSME owners with a tolerable error rate of 5%. The sampling technique with probability sampling uses simple random sampling. Data were analyzed using multiple linear regression analysis methods. The results of the research show that Entrepreneurial Behavior partially has a positive and significant effect on the success of grocery MSMEs in Medan Barat Subdistrict. Competitive Advantage partially has a positive and significant effect on the success of grocery MSMEs in Medan Barat Subdistrict. The -F test shows that Entrepreneurial Behavior and Competitive Advantage simultaneously influence the success of Grocery MSMEs in Medan Barat Subdistrict. The R Square is 0.589 or 58.9%, which means that Entrepreneurial Behavior and Competitive Advantage influence the success of Grocery MSMEs by 58.9%.